Relationship between type of cleft palate and Eustachian tube function in children, Peru 2020 - Antayhua Ortiz, Sara Isabel (2022)
Introduction and objectives: The objective of this study is to determine if the type of cleft lip and palate is associated with a higher risk of alteration of the Eustachian tube. Materials and methods: A descriptive case series study was carried out with an inferential analysis of children operated on for cleft lip and palate at the San Bartolomé hospital during the years 2018 and 2019. Results: 48 patients with tympanometry were evaluated, 62.5% male (n = 30) and 37.5% female (n = 18), the mean age was 1.3 years. The type of cleft lip and palate was determined using the Veau classification, the most frequent type found was Veau type III: 62.5% (n = 30), the least frequent type was Veau I with 4.2% (n = 2). The evaluation of the function of the Eustachian tube was performed with tympanometry, defining the type B curve as pathological. In the studygroup, there was an overall prevalence of type B curves of 66.7% (n = 32), while type A and C curves were 33.3% (n = 16). The probability that the Veau IV crack type has an association with type B curves more frequently than the other types, using the Binomial test, was significant. (p = 0.000038 <0.05). Conclusions: The type of cleft palate that is most associated with impaired middle ear function, expressed by type B tympanometry curves, is type IV cleft according to Veau's classification, this relationship is statistically significant.